Curriculum Navigation and Local Sport Wisdom in Shaping Meaningful Physical Education in Rural Primary Schools - Sugiarto, Bambang Gatot (Asian Journal of Applied Education (AJAE), 2025)
This study explores how Curriculum Navigation and local sport wisdom contribute to creating meaningful Physical Education (PE) in rural elementary schools. Using a mixed-methods approach involving literature review, field observations, and interviews with teachers, stakeholders, and practitioners, the research focuses on curriculum design that integrates local context and traditional sports. The findings show that incorporating local sport wisdom enhances student motivation, participation, motor skills, cultural identity, and social relationships. Moreover, place-based and culturally relevant pedagogy strengthens students’ sense of ownership and enriches the learning experience. The study concludes that the synergy between curriculum design and local sport traditions fosters more meaningful PE and recommends curriculum adaptation and teacher training that are responsive to local culture to improve learning effectiveness and sustain cultural values.